2015
DOI: 10.1016/j.rbmo.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Processing of semen by density gradient centrifugation selects spermatozoa with longer telomeres for assisted reproduction techniques

Abstract: The ends of eukaryotic chromosomes contain specialized chromatin structures called telomeres, the length of which plays a key role in early human embryonic development. Although the effect of sperm preparation techniques on major sperm characteristics, such as concentration, motility and morphology have been previously documented, the possible status of telomere length and its relation with sperm preparation techniques is not well-known for humans. The aim of this study was to investigate the role of density g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to compare the telomere length in sperm cells recovered by the DGC and SU methods. In our study, the STL of the spermatozoa enriched by these both methods was longer than that in raw semen, which is consistent with previous studies that have demonstrated that either the SU or the DGS method could select sperm with a longer STL and lower DNA fragmentation3536. Nevertheless, no significant difference was found between the STL in sperm obtained by the two procedures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study to compare the telomere length in sperm cells recovered by the DGC and SU methods. In our study, the STL of the spermatozoa enriched by these both methods was longer than that in raw semen, which is consistent with previous studies that have demonstrated that either the SU or the DGS method could select sperm with a longer STL and lower DNA fragmentation3536. Nevertheless, no significant difference was found between the STL in sperm obtained by the two procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Sperm DNA fragmentation was determined using a kit according to the manufacturer’s instructions (BRED, Life Science Technology Inc., Shenzhen, China), and the detailed steps are described in a previous study36. More than 500 sperm were assessed for each sample under a 100X objective on an Olympus BX51 microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, in addition to PLC-ζ or Izumo-1 distribution patterns at a high-resolution 3-D confocal microscopic level, we also analyzed the sperm morphology according to strict criteria and found no significant difference between groups in the NZS cases. Our finding that SU+MACS or DG+MACS resulted in lower DNA fragmentation and higher DNA integrity compared to SU or DG alone at the statistically insignificant level indicated that SU or DG alone are also beneficial techniques to select spermatozoa with high DNA quality as it has been indicated by previous studies [11,12]. Very recently, Bucar et al [13] demonstrated that the application of MACS following DG and SU gave a significantly lower number of total or rapid progressive spermatozoa compared to others.…”
Section: Discussionsupporting
confidence: 54%
“…Few studies have been published on STL in relation to semen parameters, and the small amount of information that is available is contradictory. Thilagavathi et al (2013) did not find any correlation with conventional sperm parameters and telomere length, whereas other studies reported a positive association between STL and sperm count in young donors (aged 18-19 years) (Ferlin et al, 2013) and in infertile patients (Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 91%